College and University Degree Programs for the Preparation of Professional Adult Educators, 1970-71 - Griffith, William S.; Cloutier, Gilles H. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
The directory of institutions providing a degree program for training adult educators was developed as an essential step in making training opportunities better known to prospective students and their advisers; the population covered includes programs omitted from prior studies. A substantial portion of the document is comprised of a listing of institutions training adult educators, with names, titles, and addresses of directors (1970-71). Information presented in tabular form includes: programs offered, geographical distribution, level of training, program designations, institutional program area emphases, internships, functions for which students were being prepared, graduates, and academic backgrounds of professors. Among 11 conclusions reached by the researchers are these: (1) individuals who responded widely misinterpreted the term "adult education;" (2) personnel are often not aware of degree programs in their institutions; (3) there are at least twice as many degree-granting institutions as indicated by the most recent survey of membership of the Commission of the Professors of Adult Education. Approximately half the document is devoted to three appendixes: a discussion of prior studies, the survey design and methodology, and the survey instructions and form. (AJ)
Availability: Superintendent of Documents, U.S. Government Printing Office, Washington, D.C. 20402 ($1.15).
Sponsoring Agency: Office of Education (DHEW), Washington, DC.
Contract Number: OEC-0-3537.
ERIC Note: For the original report see ED 058 540.
Educational level discussed: Adult Education.
May also be available online. Address as at 14/8/18
Keywords: Adult Education; Adult Educators; Colleges; Degrees (Academic); Directories; Educational Programs; Educational Research; Graduate Surveys; Institutions; Internship Programs; Program Content; Program Descriptions; Statistical Surveys; Teacher Education; Teacher Educator Education; Teacher Educators; Universities; Reference Materials, Directories/Catalogs.